A6.3 The role of micro-RNA 155 in autoimmune arthritis. (13th February 2015) - Goncalves-Alves, E; Saferding, V; Puchner, A; Benson, R; Kurowska-Stolarska, M; Brewer, J; Schliehe, C; Bergthaler, A; Smolen, JS; Redlich, K; Blüml, S
Abstract : Background: MicroRNAs are a novel class of regulatory RNAs that have been demonstrated to control several important biological processes. They have been implicated in the pathogenesis of auto-immunity; however their true contribution in these diseases it is not truly clear. MicroRNA-155 (miR-155) has been demonstrated to be present in inflamed joints of patients suffering from rheumatoid arthritis (RA) as well as being essential for the development of collagen induced arthritis (CIA). Our goal is to understand which immune cells contribute for the resistance of miR-155 deficient mice to CIA. Methods: MiR155 deficient mice were crossed into hTNFtg mice, arthritis development was evaluated. Activation and cytokine production of bone marrow derived dendritic cells (BMDC) was evaluated both in vivo and in vitro, by flow cytometry and qPCR. T cell stimulatory capacity was evaluated by mixed lymphocyte reaction with OTII T cells, containing an ovalbumin specific TCR. MiR-155 OTII deficient T cells were transferred into wild type mice or co-cultured with wild type (wt) BMDCs. Sorted naïve T cells were stimulated with anti-CD28 and anti-CD3. Results: In hTNF innate immunity dependent arthritis model we saw no difference in disease development between miR-155 -/- and wt mice. Expression of MHCII and co-stimulatory molecules after LPS stimulation was similar in miR-155 deficient and wt BMDCs. LPS treatment of wt and miR-155 -/- mice revealed similar pro-inflammatory cytokine production (TNF, IL-6 and IL-23). Furthermore, T cell stimulatory capacity of wt and miR-155 -/- was identical both in vitro and in vivo . Contrasting with the limited role in innate immune cells, miR-155 deficient T cells show a severely impaired proliferative capacity in vivo and in vitro . However, proliferation of naïve T cells was similar upon stimulation with anti-CD3 and anti-CD28 Conclusion: Although role of miR-155 in innate immunity seem to be limited, it appears that the resistance to induction of CIA come from a defect in adaptive immunity. This is seen by the reduced proliferative capacity of miR-155 deficient cells when stimulated by wt BMDCs, both in vivo and in vitro . Therefore miR-155 might represent an interesting therapy target for autoimmune diseases such as rheumatoid arthritis.